Impact of micro-environmental factors on survival, reproduction and distribution of Oncomelania hupensis snails - Mao-Mao Liu; Yun Feng; Kun Yang (BMC, 2021)
Abstract Background Schistosomiasis japonica is a chronic parasitic disease that seriously harms people's health. Oncomelania hupensis is the only intermediate host of Schistosoma japonicum. The micro-environmental factors surrounding the snail have a great impact on the survival, growth and reproduction of O. hupensis, but there are few relevant systematic analyses until the present. This scoping review aims to identify and summarize the micro-environmental factors that greatly affect O. hupensis, and to find gaps in research thus to provide directions for future in-depth studies. Main body This scoping review searched databases with search terms of the combinations of "Micro(-)environment", "Oncomelania" and their expanded aspects. A total of 133 original articles were recruited. Predefined data fields were extracted including research methods, influencing factors, and their effects on O. hupensis. Most studies focused on vegetation factors (54.1%), and other factors noted were soil composition (27.8%), water environmental factors (24.1%), and predator (3.0%), respectively. The factors with positive impacts included water level, pH value, soil temperature, soil humidity, the coverage and height of vegetation at suitable levels. This could provide more detailed information for O. hupensis habitat identification and prediction. The factors with negative impacts included plant extracts, snail control and disease prevention forests, and microorganisms with molluscicidal activities. It revealed a potential application as ecological molluscicides in the future. Factors such as physico-chemical properties of water, soil chemistry showed a gap in scientific studies, thus required further extensive research. Conclusions Micro-environmental factors including water quality, soil composition as well as the technology and application of biomolluscicides (plant extracts and microorganisms) deserve more attention. Relative study findings on micro-environment have good potentials in snail control applications. Further studies should be implemented to investigate the impact of micro-environmental factors on snails and close the research gaps.